Nutrition Value and Phytochemical Screening of Gembolo (Dioscorea bulbifera L.) Bulbils and Tubers from Bogor, West Java - Emma Sri Kuncari (Jurnal Ilmu Pertanian Indonesia, 2023)
Gembolo is often cultivated in tropical areas, mainly for its bulbils (edible aerial bulbs) and tubers. This study will discuss the nutritional value and phytochemical screening of gembolo bulbils and tubers from Bogor, West Java. There is still little information and publication about this gembolo bulbils and tubers. In addition, to reintroduce and preserve this rare plant. The research was done by exploration, direct observation, and interview, followed by laboratory analysis and literature. The methods used in the proximate analysis include moisture content (AOAC), ash content (gravimetric), fat content (soxhlet), protein content (Kjeldahl), fibre (gravimetry), and carbohydrates as starch (titrimetry). Phytochemical screening was carried out qualitatively. The proximate test results showed that bulbils had higher water, fat, and fibre content than bottom tubers. Bottom tubers have higher ash, protein, and carbohydrates as starch content than bulbils. This confirms the assumption that bottom tubers are more recommended as a source of food than bulbils and because of their larger size than bulbils. The results of phytochemical screening showed that both bulbils and gembolo bottom tubers contained the same chemical compounds, namely alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, and glycosides. Keywords: bulbil, Dioscorea, gembolo, proximate, tuber